THE MECHANISMS FOR UPDATING THE SPIRITUAL SPACE OF THE MODERN RUSSIAN SOCIETY - Lyudmila Aleksandrovna Burnyasheva (Вестник Северо-Кавказского федерального университета)
In the article the author examines the mechanisms for updating the spiritual space of the modern Russian society. Today the requirement for past revaluation is caused, first of all, by search of new reference points of existence.